The Dynamics of Vertical Coordination in Agrifood Chains in Eastern Europe and Centra Asia - Swinnen, Johan F.M. (Washington, DC : World Bank, 2012)
A major problem in the Europe and Central Asia (ECA) agricultural sector and rural areas during the transition was the breakdown of the relationships of farms with input suppliers and output markets. The simultaneous privatization and restructuring of the farms and of the up- and downstream companies in the agrifood chain have caused major disruptions. The result is that many farms and rural households face serious constraints in accessing essential inputs (feed, fertilizer, seeds, capital, etc.) and in selling their products. This report presents several case studies and survey reports implemented across countries and subsectors of the agrifood supply chains in ECA. The case studies provide detailed information and analysis and are a rich source of insights in the processes of vertical coordination that are taking place in the ECA region and their effects. In addition, the case studies include interviews with managers of international companies who have invested in this region. The objective of the study was to analyze vertical coordination (VC) in agrifood supply chains in ECA and to identify options for improved policies, institutions, and investments which Governments could make, and which the World Bank could support, in order to improve links in the agricultural marketing and processing chain and increase access of farmers to input and output markets. This is especially important in those countries where contractual arrangements are slow to develop.